Bridging research, leadership, and advocacy: A systems approach to tackling food insecurity - Ramirez, Jessica (My University, 2025)
This report summarizes my Applied Practice Experience (APE), which encompassed four distinct but interconnected initiatives: The Cats’ Cupboard (Kansas State University’s on-campus food pantry), the Alternative Breaks Program in Garden City, the Rural Grocery Initiative and Kansas Healthy Food Initiative, and the development of a SNAP Outreach Program for K-State students. Over the course of 240 applied practice hours, I gained invaluable experience in public health practice, particularly in five core competencies: leadership, governance, and management; systems thinking; structural analysis of health disparities; and data-driven program development and biostatistical analysis. These competencies provided a framework for my engagement in direct service, community-based research, policy advocacy, and leadership in public health initiatives. While these four competencies were central to my experience, in the following sections, I will also highlight how other of the 22 foundational public health competencies were addressed throughout my work. Throughout this experience, I worked under the mentorship of four key preceptors, each playing an essential role in my learning and making contributions across these projects. Shelly Williams, Director of ‘Cats Cupboard, guided me in food pantry operations, resource management, and program expansion to address food insecurity on campus. Tamara Bauer, Director of the Alternative Breaks Program, supported my facilitation of immersive student learning experience in Garden City, where I led discussions on food systems, labor, and public health. Dr. Leah Tsoodle, an agricultural economist, provided mentorship in research design and data analysis for the Rural Grocery Initiative, where I examined food access and grocery sustainability in rural communities. Dr. Kara Ross, also an agricultural economist, played a pivotal role in supporting my efforts to develop a SNAP Outreach Program for K-State students—a project that marks the first university-led SNAP outreach initiative in the state of Kansas. The primary objectives of my APE were to design and implement public health interventions that address food insecurity, apply systems thinking tools to analyze food access challenges, develop leadership and advocacy skills, and engage in data-driven decision-making to inform policy and program development. Through these four experiences, I was able to work at the intersection of research, community engagement, and policy to advance food security in meaningful ways. As part of my contributions to these initiatives, I facilitated strategic planning efforts for ‘Cats Cupboard, expanding its services and reducing stigma associated with food assistance; conducted research and data analysis for the Rural Grocery Initiative and Kansas Healthy Food Initiative, contributing to policy recommendations aimed at strengthening rural food systems; and initiated the process of establishing a SNAP Outreach Program at K-State, collaborating with a multidisciplinary team to secure funding and develop a strategic plan for implementation. This program represents a groundbreaking effort, as no other university in Kansas currently has an official SNAP outreach initiative. This culminating Applied Practice Experience allowed me to engage in impactful public health work across four different but interconnected settings, each contributing to my professional development. In the forthcoming sections of this report, I provide an in-depth examination of each organization and project, detailing my responsibilities, the public health competencies I applied and strengthened, and the broader implications of my work. As will be evident, my experience across these four sites enabled me to develop expertise in leadership, systems thinking, structural analysis of health disparities, and data-driven program development—while also practicing additional competencies in advocacy, stakeholder engagement, and program evaluation. These experiences have prepared me to continue addressing food insecurity and public health challenges through research, policy, and community-driven action.
Keywords: Food insecurity; Public health; SNAP outreach; Systems thinking; Leadership; Community engagement